2014
DOI: 10.1103/physrevc.90.061306
|View full text |Cite
|
Sign up to set email alerts
|

From the lightest nuclei to the equation of state of asymmetric nuclear matter with realistic nuclear interactions

Abstract: We present microscopic calculations of light and medium mass nuclei and the equation of state of symmetric and asymmetric nuclear matter using different nucleon-nucleon forces, including a new Argonne version that has the same spin/isospin structure as local chiral forces at next-to-nextto-leading order (N2LO). The calculations are performed using Auxiliary Field Diffusion Monte Carlo (AFDMC) combined with an improved variational wave function. We show that the AFDMC method can now be used to successfully calc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 56 publications
(113 reference statements)
4
48
0
Order By: Relevance
“…[50] S is obtained as the difference between the PNM and the SNM equations of state at a given density. For microscopic approaches (like MBPT) these two definitions of S give very similar values (see e.g., [86,87]). …”
Section: A Zero Temperaturementioning
confidence: 98%
“…[50] S is obtained as the difference between the PNM and the SNM equations of state at a given density. For microscopic approaches (like MBPT) these two definitions of S give very similar values (see e.g., [86,87]). …”
Section: A Zero Temperaturementioning
confidence: 98%
“…[37,38]. Recently, there has been new work on this subject using perturbative chiral effective field theory (EFT) [39] and auxiliary field diffusion Monte Carlo [40]. Both of these works have shown that the quadratic expansion of cold nuclear matter works very well; however, they did not constrain the fourth-order symmetry energy directly.…”
Section: Experimental Constraintsmentioning
confidence: 99%
“…For going beyond light nuclei, one can either combine these forces with standard many-body methods like the no-core-shell-model, the coupled cluster approach, and so on (for some recent such works see Refs. [5][6][7][8][9][10][11]) or develop a novel scheme that uses lattice methods to tackle the nuclear many-body problem. This is the approach I will discuss here.…”
Section: Introductionmentioning
confidence: 99%